Prevention of Depressive Symptoms and Promotion of Well-being in Adolescents: A Randomized Controlled Trial of the Smile Program: Un ensayo controlado aleatorizado del Programa Sonrisa - Sánchez-Hernández, Óscar; Méndez, Francisco X.; Ato, Manuel; Garber, Judy (Anales de Psicología / Annals of Psychology, 2019)
This study addressed the development and evaluation of the Smile Program whose main objective was the prevention of depression and the promotion of well-being in adolescents. The program is based on interventions that have been shown to be efficacious (a cognitive-behavioral approach). Participants were 89 adolescents (mean age = 13.88 years; SD = 0.95) recruited from a sample of 1212 students from seven schools. Results showed a significant reduction in self-reported depressive symptoms in the intervention group (n= 51) as compared to youth in the control group (n= 38). Based on parents’ report (n=56), youth in the intervention group had significantly better self-esteem at post-test as compared to youth in the control group. At four months post intervention, youth in the intervention group had higher psychological well-being than those in the control group; at the 8-month follow-up, youth in the intervention condition reported better family self-concept.